Pain management associated with arteriovenous fistula cannulation among children undergoing haemodialysis: Systematic review - Ririn Muthia Zukhra; Dessie Wanda (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate studies related to pain management associated with arteriovenous fistula cannulation among children. Method: The systematic review comprised literature search on Embase, ProQuest, Science Direct, Scopus, SpringerLink and Wiley Online databases for studies published in English between 1998 and 2021. The search used key words, including pain management OR analgesia AND child OR paediatric AND haemodialysis OR dialysis AND arteriovenous fistula OR arteriovenous fistula cannulation OR fistula needle OR arteriovenous fistula insertion OR needle insertion. The quality of the studies was evaluated using the Joana Briggs Institute checklist. General characteristics of the and pain outcomes were noted. Results: Of the 2,877 studies initially identified, 8(0.27%) were analysed; 7(87.5%) quasi-experimental and 1(12.5%) randomised controlled trial. Overall, there were 283 participants aged 6-18 years. The strategies used for reducing arteriovenous fistula puncture-related pain among children undergoing haemodialysis included cryotherapy, lidocaine agents, virtual reality (VR), guided visualisation, balloon inflation, aromatherapy, and other programmed distractions. The strategies had a positive effect on reducing arteriovenous fistula cannulation-related pain among children. Conclusion: Non-pharmacological pain management is an easier, simpler, inexpensive and more effective method of atraumatic care among children undergoing haemodialysis. Keywords: Dialysis, Lidocaine, Aromatherapy, Catheterisation, Fistula, Cryotherapy, Analgesia, Punctures.